Power-based resistance training reduced serum oxidized low-density lipoprotein in athletes - Koh, Y.; Miller, J. (International Journal of Sports Science, 2012)
Power-based resistance training (PRT) allows athletes to improve athletic performance by enhancing both strength and power simultaneously. However, it is unclear whether athletes who participate in PRT can positively alter serum lipid and lipoprotein parameters. Thus, the current study investigated the effects of 6-weeks of PRT on serum lipid and lipoprotein parameters in male and female collegiate athletes. Twenty one collegiate athletes (12 female soccer players and 9 male football players) participated in PRT (4 days/week) for 6 weeks. The PRT program was composed of a variety of Olympic-style and traditional weightlifting movements along with plyometrics. Overnight fasting blood samples were collected before and after 6-weeks of power-based resistance training to analyze serum lipid and lipoprotein parameters including TG, TC, VLDL-C, LDL-C, HDL-C, Lp(a), and ox-LDL. All serum lipid and lipoprotein parameters remained unchanged, except ox-LDL which significantly (p = 0.036) decreased by 3.81% or 1.87 U·L-1 (from 49.05 ± 9.17 to 47.18 ± 9.78 U·L-1) following 6 weeks of power-based resistance training. The 6-weeks of PRT, designed to improve strength and power, can provide cardioprotective health benefits for male and female collegiate athletes by lowering ox-LDL.